A race against time: couples' lived diagnostic journeys to young-onset dementia. (28th October 2022) - Grunberg, Victoria A.; Bannon, Sarah M.; Popok, Paula; Reichman, Mira; Dickerson, Bradford C.; Vranceanu, Ana-Maria
Abstract: Purpose: Young onset dementias (YOD) – typically defined by symptom onset before age 65 – are frequently overlooked in medical and community settings. Persons with YOD and their spouses face logistical and emotional challenges on their journey to a diagnosis (e.g. uncertainty about symptoms, lack of medical knowledge, emotional distress). An in-depth understanding of couples' experiences before and immediately following a YOD diagnosis is warranted to inform early psychosocial services for couples. Methods: We utilized dyadic qualitative semi-structured interviews ( N  = 23) to better understand the nuances of couples' pre-diagnostic and diagnostic experiences with YOD. We used a hybrid of deductive and inductive analytic strategies to identify couple-level themes. Results: Fifteen couple-level themes were extracted within four domains: (1) early indicators of symptoms, (2) obtaining a diagnosis, (3) experiences with health care providers, and (4) emotional reactions to the diagnosis. Couples expressed difficulties communicating about early symptoms, receiving accurate and timely diagnostic information, and managing multiple emotions. They described the value of working together to manage care, gain information, establish positive relationships with providers, and promote adjustment. Conclusion: Findings highlight the shared experiences of couples during the early stages of YOD, including the importance of strong communication with each other and providers. Early and accessible psychosocial services that help couples cope with and communicate about individual and shared stressors are warranted.